Calculation of the role of indochina countries in global warming and its consequences in the world - Tarko, Alexander; Van Lang, Tran (Vietnam Journal of Science and Technology, 2017)
This paper presents the calculation of the change cycle Carbon dioxide (CO2) in the global biosphere with the aid of spatial mathematical models. The absorption of CO2 emissions from burning fossil fuels, deforestation, and soil erosion by terrestrial ecosystems have been calculated for all countries in the world, especially the countries of Indochina. The paper also provides several experiments to evaluate simulation results based on different scenarios of implementing the Kyoto Protocol. Thereby showing the Indochinese countries have a significant role in the absorption of CO2 into the atmosphere, affecting ugly the Kyoto Protocol. The deforestation and soil erosion are the main causes